2012
DOI: 10.1002/mds.25259
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dysphagia before and after deep brain stimulation in Parkinson's disease

Abstract: Although dysphagia is a common problem for many Parkinson's disease (PD) patients, the effect of deep brain stimulation (DBS) on swallowing is unclear. Fourteen subjects with advanced PD underwent videofluorographic swallowing studies prior to bilateral DBS of the subthalamic nucleus (STN) and at 3 and 12 months postprocedure. They were tested under several stimulation and medication conditions. Subjects completed the Dysphagia Handicap Index at each time. There was a strong trend toward improved swallowing re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 22 publications
2
37
0
Order By: Relevance
“…Among the 39 deaths in this study group, the 15 cases of pneumonia, seven cases of asphyxia, and three cases of multiple-organ failure were all associated with swallowing impairments. These swallowing-related disorders are likely the result of stereotyped movement and motor impairment of the epiglottis and throat muscles 23,24. Kanna and Bhanu also reported a high prevalence of swallowing-related diseases in patients with PD, the severity of which was associated with the duration and severity of PD 25.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 39 deaths in this study group, the 15 cases of pneumonia, seven cases of asphyxia, and three cases of multiple-organ failure were all associated with swallowing impairments. These swallowing-related disorders are likely the result of stereotyped movement and motor impairment of the epiglottis and throat muscles 23,24. Kanna and Bhanu also reported a high prevalence of swallowing-related diseases in patients with PD, the severity of which was associated with the duration and severity of PD 25.…”
Section: Resultsmentioning
confidence: 99%
“…A thicker bolus will help protect airway in comparison to thin-liquid boluses through one or more of several mechanisms, including increased sensory feedback, increased bolus cohesiveness and/or slowing bolus flow through the oropharynx [41,52]. An important feature of these studies is better hydration and positive effects on patients' quality of life through inhibition from aspiration [2].…”
Section: Adding Hydrocolloids To Normal Foodsmentioning
confidence: 97%
“…In cases where drug treatment is complicated by incapacitating response fluctuations, deep brain stimulation is required -a surgical approach where electrodes are placed in the basal ganglia, most often in the subthalamic nucleus. With the exception of one case study, in which symptoms of stridor, dysphagia and aspiration were resolved when the subthalamic nucleus stimulator was switched off [58], studies have either reported no clinically relevant changes in deglutition after subthalamic nucleus deep brain stimulation [59] or an improvement of dysphagia in the 'on' condition [60][61][62], in particular in the pharyngeal stages of swallowing [63].…”
Section: Medical Treatmentmentioning
confidence: 88%